1998
DOI: 10.1002/(sici)1098-2388(199807/08)15:1<15::aid-ssu4>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of CA-19-9 in pancreatic carcinoma

Abstract: Preoperative and postoperative serum levels of carbohydrate antigen‐(CA)19‐9 in 148 patients with carcinoma of the pancreas were studied. All 18 patients with carcinoma of the pancreas of Stage I, II, and III were resectable, and their pre‐operative serum levels of CA‐19‐9 were under 1,344 U/ml. Pre‐operative serum levels of CA‐19‐9 in patients with Stage IV ranged widely between 5 and 32,240 U/ml. The postoperative survival rate was significantly superior in patients (n = 15) whose CA‐19‐9 pre‐operative serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…22 Our study confirmed that elevated serum CA 19-9 level correlates with a poor survival as corroborated by several studies. [8][9][10][11][12][13][14][15][16][17]23 Our study also found that patients with VHL (over 800 IU/ml) had equivalent survival as patients with HL. Thus, although a serum CA 19-9 level of 150 or 300 IU/ml preoperatively may discriminate between patients with good and poor outcome, 5, 12-14, 16 levels over 400 IU/ml, however high, have no additional effect on survival.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…22 Our study confirmed that elevated serum CA 19-9 level correlates with a poor survival as corroborated by several studies. [8][9][10][11][12][13][14][15][16][17]23 Our study also found that patients with VHL (over 800 IU/ml) had equivalent survival as patients with HL. Thus, although a serum CA 19-9 level of 150 or 300 IU/ml preoperatively may discriminate between patients with good and poor outcome, 5, 12-14, 16 levels over 400 IU/ml, however high, have no additional effect on survival.…”
Section: Discussionsupporting
confidence: 71%
“…12 Moreover, some investigators have found that elevated preoperative serum CA 19-9 levels are significantly associated with tumor unresectability, although the cut-off levels reported range from 100 to 350 IU/ml. [8][9][10][11][12][13][14][15][16][17] Based on these data, some speculate that preoperative staging of a potentially resectable PA should routinely include serum CA 19-9 levels after biliary decompression. In the case where careful preoperative staging indicates a radiographically resectable PA without evidence of distant metastasis but the serum CA 19-9 levels are highly elevated, the staging might be better clarified by the use of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 The relationship between increases in CA 19-9 and poor survival is well documented. [4][5][6][7] Numerous studies have shown that CA 19-9 is associated not only with resectability but also with tumor stage in pancreatic cancer. [8][9][10] In fact, Schlieman et al 8 suggested that an increased CA 19-9 level is predictive of unresectability at the time of exploration even when there is no evidence of unresectability on preoperative imaging studies.…”
Section: Introductionmentioning
confidence: 99%